A thermodynamic model for simultaneous growth of gas and solid phases from gas saturated melt. (December 2015) - Lu, Ya; Wen, Zhichun; Jin, Qinglin; Jiang, Yehua
Highlights: Gas-metal eutectic is controlled by independent growth of gas and solid phases. A thermodynamic model is developed to describe the pore structure. The calculated values of the model are compared with the experimental results. Abstract: Production of ordered porosity materials by directional solidification is characterized by simultaneous growth of solid and gas phases from gas supersaturated melt. It is considered that the formation of ordered porosity is controlled by two independent processes: one is the hydrogen diffusion controlled growth of gas phase; and the other is the thermal diffusion controlled growth of solid phase. A simple thermodynamic model is developed to describe the relationship between the processing and the pore structure. The model is applied for the ordered porosity copper fabricated by directional solidification. The deviation between the calculated and experimental values is discussed with respect to the characteristics of hydrogen diffusion in liquid metal.